AB0648 CORRELATIONS BETWEEN NEUTROPHIL/LYMPHOCYTE RATIO AND CLINICAL CHARACTERISTICS OF PATIENTS WITH SYSTEMIC SCLEROSIS. (June 2019) - Giovanna, CUOMO; Masini, Francesco; Gjeloshi, Klodian; Guarino, Francesco; Danzo, Fiammetta; Adinolfi, Luigi Elio; Romano, Ciro
Abstract : Background: The ratio of neutrophils to lymphocytes (NRL) is considered a novel inflammatory marker. Recently studies are ongoing for objective and easy markers (1) Objectives: In this study, we aimed to identify the possible relationship between NRL and clinical characteristics inn patients with systemic sclerosis (SSc) Methods: Our study is based on a retrospective analysis. We collected in a data base clinic and epidemiological characteristic of SSc patients. Fifty-two patients (46 female; 10 subset diffuse) with SSc were enrolled consecutively for analyser the correlations. We considered the correlation with NRL and skin core, ulcers, pitting scars, gastro-intestinal events, fibrosis on HTCR, respiratory parameters (FVC, DLCO), PAPs, diastolic abnormalities, capillaroscopy alterations and activity index (2). Student's t-test was used for comparison averages, correlation among variables were assessed by Sperman's correlation testing. Results: sociodemographic and clinical characteristic were reported in table 1 . The correlation analysis statistically significant is summarized in table 2 : NLR vs skin score, DLCO, PAPs, and activity index. The correlation analysis between NLR and presence of ulcers and pitting scars was considered not quite significant. There were no correlations between other parameters and NLR. Conclusion: NLR values correlated negatively with DLCO value, and positively with PAP value, skin score and activity index NLR level may serve as inflammatory marker in patients with SSc. References: [1] absenger G. et al. Br J Cancer2013; 109:395 [2] Valentini G. et al. Ann Rheum Dids2001; 60:592 Disclosure of interests: None declared